2021
DOI: 10.1002/jcop.22561
|View full text |Cite
|
Sign up to set email alerts
|

Stress of university students before and after campus closure in response to COVID‐19

Abstract: Due to the COVID-19 pandemic, universities were forced to adopt a remote learning model, which introduced a number of stressors into college students' everyday life and study habits. The current study investigates if students' study-related stress increased after the pandemic's onset and how individual and contextual factors moderate this potential stress increase. Longitudinal survey data about students' stress levels and self-efficacy in self-regulation were collected before and after the onset of the COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 51 publications
6
94
0
2
Order By: Relevance
“…On the other hand, evidence across the world indicated that the younger people including children were vulnerable to the mental health problems during the Covid-19 pandemic [7][8][9]. Indeed, most recent studies have revealed that the university students were suffered from more psychological stress and experienced more depressive and anxiety symptoms during the pandemic due to the lockdown, uncertainty and life disruption [10,11]. Among them, medical students deserve special attention during the pandemic, as they are the future healthcare professionals, and the negative impact of Covid-19 may influence their future career choice [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, evidence across the world indicated that the younger people including children were vulnerable to the mental health problems during the Covid-19 pandemic [7][8][9]. Indeed, most recent studies have revealed that the university students were suffered from more psychological stress and experienced more depressive and anxiety symptoms during the pandemic due to the lockdown, uncertainty and life disruption [10,11]. Among them, medical students deserve special attention during the pandemic, as they are the future healthcare professionals, and the negative impact of Covid-19 may influence their future career choice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it would not be practical to provide equal support to all students; however, it would be practical to support those who are at a high risk of mental illness and are in need of help. Previous studies showed that women ( Nomura et al, 2021 , Patsali et al, 2020 , Wathelet et al, 2020 ), who had lower social support or were isolated ( Kohls et al, 2021 , Elmer et al, 2020 ), with lower self-efficacy ( Kohls et al, 2021 , von Keyserlingk et al, 2021 ), and having a mental disorder or suicidal behavior ( López Steinmetz et al, 2021b ), had a higher risk of psychological distress.…”
mentioning
confidence: 99%
“…For example, students with poorer mental health perceive less support from their teachers (Tinklin et al, 2005;Rubach et al, 2020). In addition, poorer mental health also leads to less satisfaction and more stress if associated mental health impairments have not been adequately treated (Lipson and Eisenberg, 2018;von Keyserlingk et al, 2021). These results support the theorized bi-directional links between social support, psychological states, such as satisfaction and stress, and mental health as described in the main effect model (Cohen and Wills, 1985;Cohen et al, 2000).…”
Section: The Concept Of Instructional Qualitymentioning
confidence: 60%
“…Investigating such bi-directional effects is essential for research on the impact of the COVID-19 pandemic on students' academic development. In terms of stress, the COVID-19 pandemic has caused increased stress among university students on multiple levels (von Keyserlingk et al, 2021). The future health impacts of the COVID-19 pandemic remain unknown.…”
Section: The Concept Of Instructional Qualitymentioning
confidence: 99%